Using Top and Tail Game to Improve Students’ Vocabulary Mastery - Permatasari, Yovita Dyah (Universitas Muhammadiyah Jember, 2019)
The aimed of this study was to show the empirical evidence about the improvement of the students’ vocabulary mastery through Top and Tail Game at the eighth grade students of MTs Negeri 1 Sumberbaru in 2018/2019 academic year. The subject of this study was VIII students of MTs Negeri 1 Sumberbaru. The research method is used classroom action research (CAR) which follows the design of Kurt Lewin. This research was conducted in two cycles. This research was carried out for one month. Techniques of data collection were interviews, observation, and test. The findings of the research showed that, the firs cycle has not achieved the criteria of success, which is the mean of 70. It was reflected that the students’ response were not observable yet when being taught by using Top and Tail Game as a new media in vocabulary. Moreover, the teacher has difficulties in teaching vocabulary by using Top and Tail Game. In the second cycle, the criteria of success was achieved. The result of this study was the implementation of learning English vocabulary through top and tail game has increased. Based on the result, it can be concluded that using top and tail game at the eighth grade students of MTs Negeri 1 Sumberbaru can improve students’ vocabulary mastery. The result of this research shows that there is an improvement in students’ vocabulary mastery.